New records of seven species of pholcid spiders (Araneae, Pholcidae) from the northern Argentina - Torres, Victor Manuel (2014)
We report new records of pholcid species for northern Argentina. Guaranita yaculica Huber, 2000 and Mesabolivar uruguayensis Machado Laborda, Simó & Brescovit, 2013 are reported for the first time for Corrientes province, whereas Aymaria calilegua Huber, 2000 and Nerudia atacama Huber, 2000 are for the first time reported for Salta province. The last corresponds to a new record for Argentina. We also expand the known distribution of Guaranita goloboffi Huber, 2000, Chibchea salta Huber, 2000, and Pholcus phalangioides (Fuesslin, 1775) for Salta province.